Kesiapan Ibu Dalam Perannya Sebagai Pendidik Anak Untuk Mempersiapkan Masa Depan Bangsa - Aziza, Noer; Hantono, Dedi (PSGA LP2M IAIN Pontianak, 2023)
The role of mothers in the family environment plays a quite dominant role in terms of children's education that makes a mother hold high responsibility in the progress of a nation. Therefore, a mother is required to have high self-quality to be able to educate future generations. But in reality in Indonesia there are still many quality mothers who still do not meet the needs and eligibility as a teacher in a household. For this reason, this study wants to find the level of quality of children's education from the role of a mother by conducting a study of the data obtained and found solutions to improve the quality of the mother. The results of this study indicate that with some actions will provide a positive thing for the quality and role of mothers in realizing the future of the nation through the future of a child as the successor generation of his nation.